003 Improving patient and family education: development of a mobile application (App) to provide personalised physiotherapy instruction. (December 2018) - Koupanou, K; Zhou, Y; Liu, X; Mohamedally, D; Conner, S; Sebire, NJ; Harniess, P
Abstract : Background: Children attending Great Ormond Street Hospital (GOSH) often have complex and highly individual therapy requirements and traditionally instruction is provided verbally and in paper form. Aim: The aim of this study was to create a mobile application that would allow healthcare professionals, in this exemplar case physiotherapists, to record and personalise therapy instruction, including video demonstrations, for use by parents at home. Methods: We developed a cross-platform mobile application using Ionic Mobile Development Framework, coding done with Visual Studio. HTML, CSS and typescript and Ionic creator were used for front-end development with node.js and the SQLite used to store data locally. Results: We demonstrate a working prototype of the customised patient information app which allows personalised recording of instructions to be made on the patient/parents' device. We demonstrate the use of a healthcare professional 'Record Video' button to access the camera to take a video (<1 min) which is saved locally, and an 'Exercise' button for patients and families to access exercises and information, in addition to the ability to add their own comments. The app provides the ability for patients and families to follow personalised demo videos and instructions for physiotherapy exercises and add their own comments for discussion at future consultations. Conclusion: Further work is required to develop the UI, resize the video player according to recording type and expand the provider information type features. Furthermore, it is planned to add a recording system such that after every exercise has been performed the patient could 'complete' this exercise for the day and rate how he/she felt about it, also allowing a diary function linked to comments and/or other patient-reported outcomes.